Influence of ACE and ACTN-3 polymorphisms on time of performance in world's off-road tiathlon race - Massidda, M.; Corrias, L.; Calo, C. M. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Triathlon is a 3-event endurance sport composed by swimming, cycling and running that are performed by athletes subsequently. The three events are separated each other by a transition period of only few seconds. A scarce number of studies have examined the influence of genetic factors on final results during an international competition. The aim of this study was to identify the single and combined influence of two polymorphisms (ACE and ACTN-3) on times of performance in a off-road Triathlon race. A simple random sample of twenty-six male athletes were selected from the two-hundred-sixty participants at the world stage of the "X TERRA World Championship". All selected athletes have completed the World`s off-road triathlon race and the Swim Time (S), the Bike Time (B), the Run Time (R), the Transition Time between S and B (T1) and Transition Time between the B and R (T2) were recorded for each athlete using the SYNOPSIS GPS system (T4 model). Correlation between genotypic and phenotypic factors was computed. Forward stepwise multiple regression models were used to explore the predictive role of each genotypic (ACE and ACTN-3) and phenotypic (S, B, R, T1, T2) variables for the final race time (FT). The ranges of the time for each event were the follows: S(min)=18-21; B(min)=86-103; R=35-45; T1(s)=26-48; T2(s)=25-53; FT(h)=2.24- 2.49. We found a significant correlation between polymorphisms and S (ACE, r=0.65; ACTN-3, r=0.60) and T2 (ACE, r=0.71; ACTN-3, r=0.79). The athletes with ACTN-3 R577X and ACE I/D genotypes have performed better time in both S and T2. The 85% of the FT variability was explained by the B (R2adj=.8566, F=143.44, df=1, p<0.01). The second most important variable was the R (R2adj=.9780, F=557.10, df=2, p<0.01), followed by the S (R2adj=.9996, F=22531.30, df=3, p<0.01). The combined influence of genotypic traits explained only the 0.03% of the FT variability. Our results suggest that the ACE and ACTN-3 polymorphisms have a significant influence on time spent swimming during off-road triathlon competition. Nevertheless, our data also highlight that the best predictor of the final race time was the time spent cycling. On the bases of our data, we conclude that the ACE and ACTN-3 polymorphisms are not determinant factors for the success in a off-road triathlon race.